2022
DOI: 10.1111/add.16030
|View full text |Cite
|
Sign up to set email alerts
|

Opium tincture versus methadone for opioid agonist treatment: a randomized controlled trial

Abstract: Aim To test if opium tincture (OT) was non‐inferior to methadone in retaining participants in opioid agonist treatment (OAT). Design A Phase III, multi‐centre, parallel‐group, non‐inferiority, double‐blind randomized controlled trial with an allocation ratio of 1:1. Participants were provided treatment and followed for a period of 85 days. Setting Four OAT clinics in Iran. Participants Two hundred and four participants with opioid use disorder [mean age (standard deviation) = 37.4 (9.3); female 11.3%] recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The present study found a relapse rate of 16.7% in opium addict patients under opium tincture therapy during the one-year follow-up, which is relatively low compared to other investigations, with relapse rates from 29 to 75% using different protocols and follow-up duration ( 33–35 ). Although methadone was identified to be better than opium tincture in keeping patients in treatment, patients’ self-reported drug use was lower with opium tincture ( 36 ). A survey on Iranian with substance use disorder has reported that 28.6% of subjects referred to drug rehabilitation centers had a history of drug rehabilitation, and a higher relapse rate was observed in patients who used modern drugs than traditional ones ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study found a relapse rate of 16.7% in opium addict patients under opium tincture therapy during the one-year follow-up, which is relatively low compared to other investigations, with relapse rates from 29 to 75% using different protocols and follow-up duration ( 33–35 ). Although methadone was identified to be better than opium tincture in keeping patients in treatment, patients’ self-reported drug use was lower with opium tincture ( 36 ). A survey on Iranian with substance use disorder has reported that 28.6% of subjects referred to drug rehabilitation centers had a history of drug rehabilitation, and a higher relapse rate was observed in patients who used modern drugs than traditional ones ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compulsory detoxification indicated an overall relapse rate of 47.6% in drug abstainers, with a survival time of 220 days to relapse ( 37 ). Comparing opium tincture and methadone in a phase III clinical trial has also indicated a lack of non-inferiority of opium tincture to methadone for retaining patients in opioid agonist-used treatment ( 36 ). Another cross-sectional study reported the retention rate with methadone and opium tincture, and buprenorphine to be 84.5, 71.8, and 90.1%, respectively, and opium tincture performed significantly better ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nikoo and colleagues report the results of a multi‐center, non‐inferiority, double‐blind randomized controlled trial (RCT) comparing the efficacy of opium tincture (OT) with methadone for maintenance treatment of individuals with opioid use disorder (OUD) [1]. Access to opioid agonist treatments (OATs) with methadone or buprenorphine is the cornerstone of national responses to OUD epidemics in many countries [2]; however, not all patients with OUD respond to these treatments [3].…”
mentioning
confidence: 99%
“…Nikoo et al . have discussed the possibility that a modified OT treatment protocol using a higher induction and maintenance dose and more frequent dosing might improve retention in the OT group [1]; however, there are several practical issues with splitting OT doses three times a day. The Iranian national protocol on OT maintenance treatment does not allow take‐home during the early stages of the treatment, and more frequent dosing approaches necessitate more frequent clinic visits to receive OT doses under direct supervision, which would be impractical for most patients and non‐viable because most centers are only open for limited hours during the morning and afternoon.…”
mentioning
confidence: 99%